Early family experiences, narcissistic traits and adjustment in emerging adulthood - Hanzec Marković, Ivana; Vujnović Malivuk, Kristina; Wertag, Anja (Psihološka istraživanja, 2019)
Exposure to risky family environment during childhood affects diverse mental health outcomes in adulthood. Recent studies have found associations between narcissistic personality traits and retrospective accounts of early experiences. However, it is important to distinguish between two forms of narcissism: the grandiose (characterized by grandiosity, aggression, and dominance) and the vulnerable narcissism (characterized by a defensive and insecure grandiosity that obscures feelings of inadequacy, incompetence and negative affect) because some aspects of narcissism are more strongly related to psychological wellbeing than others. Therefore, our goal was to examine the relationship between early risky family experiences, individual’s narcissistic traits and adjustment in emerging adulthood. Moreover, we wanted to examine narcissistic vulnerability and grandiosity as possible mediators between early risky family experiences and current adjustment (wellbeing and distress). Data was collected on a total of 348 university students in Croatia (294 female, Mage = 21.57, SD = 2.91) in an online study. The hypothesized mediation model was tested using path analysis and showed good fit to the data. Early risky family experiences positively predicted both grandiose and vulnerable narcissism, and also directly negatively predicted one’s personal wellbeing and positively one’s distress. Furthermore, vulnerable narcissism positively predicted distress and negatively predicted one's wellbeing, while grandiose narcissism did not predict any indicator of adjustment. Therefore, the hypothesis regarding the mediating role of narcissistic traits was only partly confirmed. In sum, the results show theoretically meaningful connections between psychological adjustment, narcissistic traits and early experiences, reiterating the importance of distinguishing between two forms of narcissism.
Keywords: distress; wellbeing; grandiose narcissism; vulnerable narcissism; family experiences; narcissism; Adjustment